Pharmacological analysis of neuroprotective action of methylprednisolone with citicoline in conditions of experimental allergic encephalomyelitis - Nefedov, A. A.; Mamchur, V. I.; Abramov, A. V.; Bukhtiyarova, N. V.; Абрамов, Андрій Володимирович; Бухтіярова, Ніна Вікторівна (Bulgaria: Hikari Ltd, 2016)
The paper is devoted to studying the neuroprotective effects of the integrated use of methylprednisolone with citicoline on the processes of energy providing of the mitochondria of neurons of the cerebral cortex and histomorphometric indices in experimental allergic encephalomyelitis. Cooperative administration of the drugs has a significant effect on the mitochondrial dysfunction (reduction in speed of opening of mitochondrial pores, increasing the charge of the inner membrane) and energy metabolism of the brain (increased levels of ATP and ADP, reduced lactate, increase pyruvate and isocitrate). The combined use of methylprednisolone with citicoline limits unproductive activity of anaerobic glycolysis and increases the aerobic reaction.
Keywords: experimental allergic encephalomyelitis; citicoline; methylprednisolone; mitochondria; neurons